Setting the Deadline for Determining Suspects: A Comparative Study of the Draft Code of Criminal Procedure and the Code of Criminal Procedure - Riani, Rahmahwati Silvia; Bawaeda, Adi Freddy (Bacarita Law Journal, 2025)
This article discusses the regulation on the limit for suspect determination based on the Indonesia Criminal Procedure Code Draftand the Code de procédure pénale (French Criminal Procedure Code). The purpose of this article is to determine the regulation on the time limit for suspect determination based on the Indonesian Criminal Procedure Code Draft and the French Criminal Procedure Code. This research uses a normative legal method wit a statutory, conceptual, and comparative approach. Result of this study are the French Criminal Procedure Code Draf has not explicity regulated the time limit for suspect determination, while the French Criminal Procedure Code regulates the time for suspect determination, which a maximum of 2 (two) years. The implication of not regulating the time limit for suspect determination will violate the principle of due process of laaw and universal human rights and the occurrence of arbitrary law enforcement officers in enforcing criminal procedure law.